Small-Molecule Donor/Polymer Acceptor Type Organic Solar Cells: Effect of Terminal Groups of Small-Molecule Donors - Miao, Junhui; Meng, Bin; Liu, Jun; Wang, Lixiang (Organic Materials, 2019)
Small-molecule donor/polymer acceptor type (MD/PA-type) organic solar cells (OSCs) have the great advantage of superior thermal stability. However, very few small molecular donors can match polymer acceptors, leading to low power conversion efficiency (PCE) of MD/PA-type OSCs. In this work, we studied the effect of terminal groups of small molecular donors on the optoelectronic properties and OSC device performance of MD/PA-type OSCs. We select a benzodithiophene unit bearing carbazolyl substituents as the core, terthiophene as the bridging unit, and electron-withdrawing methyl 2-cyanoacetate, 3-ethylrhodanine, and 2H-indene-1,3-dione as the terminal groups to develop three small-molecule donors. With the increase of the electron-withdrawing capability of the terminal groups, the small molecular donors exhibit redshifted absorption spectra and downshifted LUMO levels. Among the three small-molecule donors, the one with 3-ethylrhodanine terminal group exhibits the best photovoltaic performance with the PCE of 8.0% in MD/PA-type OSCs. This work provides important guidelines for the design of small-molecule donors for MD/PA-type OSC applications.
Keywords: Small-molecule donor; organic solar cells; optoelectronic properties